Instant Abdominal Wall Reconstruction with Biologic Mesh following Resection of Locally Advanced Colonic Cancer - Oskay Kaya; Engin Olcucuoglu; Gaye Seker; Hakan Kulacoglu (Case Reports in Medicine)
We present a case of immediate abdominal wall reconstruction with biologic mesh following the resection of locally advanced colonic cancer. The tumor in the right colon did not respond to neoadjuvant chemotherapy. Surgical enbloc excision, including excision of the invasion in the abdominal wall, was achieved, and the defect was reconstructed with porcine dermal collagen mesh. The patient was discharged with no complication, and adaptation of the mesh was excellent at the six-month followup.